De l’étiquette à la marque : la labellisation comme unificateur des projets territoriaux ? - Valia Filloz; Valérie Colomb (Développement Durable et Territoires)
Labelling, label and label evolution in cultural and touristic domains offer many laboratories to seize the speeches and the singular practices of sustainable development on territories. They impulse practices which spread until becoming standard, certification or brand. Label distinguishes and qualifies a territory. We examine how links between tourism, culture and territory built themselves, how the notion of sustainable development took shape in the framework texts (stakes and targets) about tourism and culture, to see finally which processes, from a representative sample, lead labels to set up concretely a new interdependence order on sustainable territories.